Unilateral Pedicle Stress Fracture in a Long-Term Hemodialysis Patient with Isthmic Spondylolisthesis. (8th February 2015) - Maruo, Keishi; Tachibana, Toshiya; Inoue, Shinichi; Arizumi, Fumihiro; Yoshiya, Shinichi
Abstract : Most unilateral pedicle stress fractures occur on the contralateral side of patients with unilateral spondylolysis. However, there are few reports of unilateral pedicle stress fractures in patients with bilateral spondylolysis and spondylolisthesis. We report a unique case of unilateral pedicle stress fracture in a long-term hemodialysis patient with isthmic spondylolisthesis. A 65-year-old man who had undergone hemodialysis presented with lower back pain that had persisted for several years. The patient experienced severe right lower extremity pain with no history of trauma. Computed tomography revealed unilateral pedicle fracture with bilateral L5 spondylolysis and spondylolisthesis with progression of scoliosis. The patient underwent Gill laminectomy of L5 with pedicle screw fixation at L4-S1 and interbody fusion at L5-S1. The patient's leg pain ceased immediately, and he began walking without leg pain. In our present patient, development of scoliosis caused by destructive spondyloarthropathy may have contributed to a unilateral pedicle fracture.